Penyelesaian Sengketa Tanah yang Belum Bersertifikat melalui Mediasi oleh Badan Pertanahan Nasional - Wita Sari Peranginangin; Devi Siti Hamzah Marpaung (Widya Yuridika, 2022)
Settlement of land disputes can be resolved through litigation or non-litigation. Dispute resolution that is resolved through litigation is very common if the problem or dispute faced is so concrete and needs to be resolved in court. However, it is possible that the problem can also be resolved non-litigation, such as by mediation, arbitration, negotiation, conciliation, or expert judgment. Alternative dispute resolution by mediation is a method that is often used in resolving disputes, especially in land disputes. The existence of a certificate of land rights is something that must be owned at this time as a valid proof of ownership of land rights. However, until now there are still many residents who have not received land rights certificates and are prone to disputes. This study aims to find out how to resolve land disputes that have not been certified and whether these disputes can be carried out using mediation methods at the National Land Agency. Seeing many of the same disputes that often occur in Indonesia. This research refers to normative juridical research which aims to determine the management of mediation in the National Land Agency.